PI 3-Kinase and the Histone Methyl-Transferase KMT2D Collaborate to Induce Arp2/3-Dependent Migration of Mammary Epithelial Cells - Karina D. Rysenkova; Julia Gaboriaud; Artem I. Fokin; Raphaëlle Toubiana; Alexandre Bense; Camil Mirdass; Mélissa Jin; Minh Chau N. Ho; Elizabeth Glading; Sophie Vacher; Laura Courtois; Ivan Bièche; et al. (Cells, 2024)
Breast cancer develops upon sequential acquisition of driver mutations in mammary epithelial cells; however, how these mutations collaborate to transform normal cells remains unclear in most cases. We aimed to reconstitute this process in a particular case. To this end, we combined the activated form of the PI 3-kinase harboring the H1047R mutation with the inactivation of the histone lysine methyl-transferase KMT2D in the non-tumorigenic human mammary epithelial cell line MCF10A. We found that PI 3-kinase activation promoted cell-cycle progression, especially when growth signals were limiting, as well as cell migration, both in a collective monolayer and as single cells. Furthermore, we showed that KMT2D inactivation had relatively little influence on these processes, except for single-cell migration, which KMT2D inactivation promoted in synergy with PI 3-kinase activation. The combination of these two genetic alterations induced expression of the ARPC5L gene that encodes a subunit of the Arp2/3 complex. ARPC5L depletion fully abolished the enhanced migration persistence exhibited by double-mutant cells. Our reconstitution approach in MCF10A has thus revealed both the cell function and the single-cell migration, and the underlying Arp2/3-dependent mechanism, which are synergistically regulated when KMT2D inactivation is combined with the activation of the PI 3-kinase.